Large-scale CO2 transport and storage infrastructure development and cost estimation in the Netherlands offshore. (July 2022) - Wildenborg, Ton; Loeve, Daniël; Neele, Filip
Abstract: A plan was developed for large-scale transport and storage of CO2, inspired by the measures in The Netherlands Climate Agreement to reduce greenhouse gas emissions to the atmosphere. The main focus was on reduction of CO2 emissions captured from large industrial sources in the Rotterdam harbour area (Rijnmond region). CO2 storage potential is available within depleted gas fields in the Dutch sector of the North Sea. Specific attention was given to the potential for re-use of existing oil and gas infrastructure and the costs and development time of the re-used or new build infrastructure for CO2 transport and storage. The study revealed that depleted gas fields in The Netherlands offshore provide ample storage capacity to accommodate a supply of 10 million tonnes (Mt) CO2 per year by 2030 and for a subsequent period of 40 years. An average total unit technical costs for compression, transport and storage was calculated at €8.6 per tonne CO2 . Concurrent operation of four to five reservoirs will be needed if the required 5 Mt annual injection rate in the base case scenario is to be met and eight to nine reservoirs need to be in operation simultaneously with a target rate of 10 Mt per year. In the accelerated case of injection of 10 Mt per year individual reservoirs will be brought on-stream much earlier than in the base case scenario. This can be up to several decades earlier for the reservoirs deployed in the final phase of CO2 storage activities.